Adoption of stress-tolerant rice varieties in India and Bangladesh: Impacts on households' income, consumption and food security - CGIAR Research Program on Rice (2020)
The meso-level analysis measures adoption of stress-tolerant rice varieties and their impact on production using exogenous weather conditions, the density of green vegetation, and a geo-spatial difference-indifference framework to identify changes in vegetative indices that occur due to the introduction of stress-tolerant rice varieties. The micro-level analysis measures adoption of stress-tolerant rice varieties and their impact on income, consumption, and food security using newly collected household data that extends an existing panel.